Homogeneous Real (2,3,5) Distributions with Isotropy - Willse, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We classify multiply transitive homogeneous real (2,3,5) distributions up to local diffeomorphism equivalence.